"A força que nunca seca": narrativas sobre performatividades de professoras/es/ies dissidentes de escolas públicas - Alves, José Ricleberson Vieira (2021)
The new profile of Contemporary Applied Linguistics, which is critical, transgressive (PENNYCOOK, 2006), Indisciplinary and mestizo (MOITA LOPES, 2006b), is an interdisciplinary/transdisciplinary movement, whose researchers seek the creation of intelligibility on social problems from a perspective of language that is understood as performance (AUSTIN, 1990) or social practice (MOITA LOPES, 2006b) and that’s why it has a central role in order to talk about the current world. Since it is situated in transgression, indiscipline and miscegenation, this study aims to analyze, through narratives, how the identity performances of dissident teachers of public schools are constructed discursively. Thus, this research draws attention to the existence of the inseparable relationship between identity performances and narratives, because people, when narrating themselves, can reinforce and also recreate who they are (WORTHAM, 2000; MELO; MOITA LOPES, 2014). Based on a queer perspective, identities are not understood, in this study, as preformed, but as performative (BUTLER, 2019a); PENNYCOOK, 2004), since they are produced in language. Thus, performativity (BUTLER, 2019a), as a discursive modality that constructs the subjects, is a possibility of deterritorialization of the "natural" and "essential" character of gender, implying the repeated stylization of the bodies, always within the systems of regulation (BUTLER, 2019a), and also in transformation and subversion. In this sense, performativity puts all gender performances in suspicion, since they are fictional and because they are produced through repeated stylizations. Therefore, in the light of a queer perspective and post-critical studies in education, I adopted the (auto)biographical research as a methodology, with a qualitative and interpretative nature for the generation and interpretation of the data, with emphasis on the narratives (ABRAHÃO, 2004), as well as on narrative interview and questionnaire as data collection instruments for understanding the life trajectories of dissident teachers, whose gender performances resist the production of cisheteronormativity in school daily life. Considering this, I understand this study as performative, since it reverses insults in a political and proud sense, because it narrates forms of existence differently from the depreciated and essentialized way they had been narrated in the past.